Evaluación química y biológica del efecto de extractos de plantas contra Plasmodium berghei - Castro, Oscar (1996)
Extracts from thirteen species of plants were evaluated by "in vivo" antimalarial test against Plasmodium berghei effects. Significant activities were observed in the ethyl acetate and aqueous extracts, elaborated of Cedrela tonduzii leaves, Trichilia havanensis and Trichilia americana bades, Neurolaena lobata and Gliricidia sepium leaves and Duranta repens fruits. Compounds identified include flavonoids, coumarins, mellilotic acid and iridoids which sorne kind of biodinamic activity has previously been reported. The flavone quercetin 1 purified from C. tonduzii gave strong antimalarial activity, however, its respective glicosides (quercetin 3-glucoside 2 y robinine 7) showed little significant activity.